A proposal for a new international debt framework (IDF) for the prevention and resolution of debt crisis in middle-income countries - Berensmann, Kathrin,Schroeder, Frank (online, 2006)
Abstract:
urn:nbn:de:0168-ssoar-193780
Keywords: (stw)Schuldenmanagement; (stw)IWF-Kredit; (stw)Internationale Wirtschaftspolitik; (stw)Welt; (stw)Schwellenländer; (thesoz)Verschuldung; (thesoz)Finanzwirtschaft; (thesoz)Gläubiger; (thesoz)IMF; (thesoz)Kooperation; (thesoz)internationale Zusammenarbeit; (thesoz)Wertpapier; (thesoz)Entwicklungsland; (thesoz)Argentinien; (thesoz)Kredit; (thesoz)Industriestaat; (lcsh)Debts; External; (lcsh)International finance; (lcsh)Financial crises; (lcsh)Argentina–Economic conditions; Graue Literatur; Debt Management; Bereitschaftskreditabkommen; Bereitschaftskredit; Internationale Wirtschaftspolitik; Emerging Market